User perceptions of social questions and answer websites for library reference services. Issue 3 (1st June 2015) - Deng, Shengli; Zhang, Yin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to understand Social Questions & Answers (SQA) users' perceptions of library reference services. Design/methodology/approach – The authors examined the postings on the largest SQA site, Yahoo! Answers, regarding library reference services and identified the major themes. Findings – Three themes emerged in library reference-related discussions: reference librarians and their services are well and positively recognized, reference services are less recognized and understood and Yahoo! Answers is recognized as a helpful service. Those who have used both library reference services and Yahoo! Answers are fully aware of the differences between the two services. Originality/value – This study provides new insights on how library reference services are perceived by SQA users. The results are helpful for libraries to position reference services to better serve users in today's information environment.